ANALISIS KEBIJAKAN PERUMUSAN SANKSI PIDANA DENDA DALAM KUHP - Eka Juarsa (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
AbstractThe writing of this journal is motivated by aspects of criminal law policy, the phenomenon of criminal use of deprivation of liberty (imprisonment) that seems